Short-term efficacy of stenting as a rescue therapy for acute atherosclerotic occlusion in anterior cerebral circulation - Wang, Jianyi; Shang, Suhang; Dun, Wanghuan; Chen, Chen; Gao, Fan; Yu, Jia; Han, Jianfeng; Liu, Fude (Frontiers in Neurology, 2023)
Purpose The study aimed to explore the efficacy and safety of the Neuroform EZ stent in treating acute anterior circulation large artery occlusion. Methods The clinical data of 42 consecutive patients with acute anterior circulation large atherosclerotic occlusion who were treated with the Neuroform EZ stent from January 2018 to August 2019 in our stroke care center, including baseline characteristics, images, therapeutic condition, and follow-up data were retrospectively analyzed. Results There were 42 mechanical thrombectomy (MT) failure cases of intracranial atherosclerotic stenosis with rescue Neuroform EZ stent implantation, of which 78.6% (33/42) had a good prognosis and 88.1% (37/42) showed no re-stenosis at follow-up. The average time from puncture to recanalization is 79.50 ± 14.19 min. The successful rate of intraoperative stent release is 97.6%, while there is one case of stent displacement, three cases of thrombus escape, and six cases of hemorrhage. Conclusion Rescue therapy of the Neuroform EZ stent for acute anterior circulation large atherosclerotic occlusion can archive good short-term imaging and clinical results, while long-term follow-up is still needed to verify.